2016
DOI: 10.3389/fneur.2016.00116
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Is Altered in Concussed Adolescent Athletes Despite Medical Clearance to Return to Play: A Preliminary Report

Abstract: Recovery following sports-related concussion (SRC) is slower and often more complicated in young adolescent athletes than in collegiate players. Further, the clinical decision to return to play is currently based on symptoms and cognitive performance without direct knowledge of brain function. We tested the hypothesis that brain functional connectivity (FC) would be aberrant in recently concussed, asymptomatic athletes who had been cleared to return to play. A seed-based FC analysis measured the FC of the defa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 27 publications
(39 reference statements)
0
39
0
Order By: Relevance
“…Increased FC in cortical areas implicated in the DMN has been previously reported in other conditions such as early stages of MS, Clinically Isolated Syndrome and mild traumatic brain injury, which share with FD a diffuse, although mild, involvement of WM (Hawellek, Hipp, Lewis, Corbetta, & Engel, ; Newsome et al, ; Roosendaal et al, ; Sharp et al, ).…”
Section: Discussionmentioning
confidence: 64%
“…Increased FC in cortical areas implicated in the DMN has been previously reported in other conditions such as early stages of MS, Clinically Isolated Syndrome and mild traumatic brain injury, which share with FD a diffuse, although mild, involvement of WM (Hawellek, Hipp, Lewis, Corbetta, & Engel, ; Newsome et al, ; Roosendaal et al, ; Sharp et al, ).…”
Section: Discussionmentioning
confidence: 64%
“…They propose that this response reflects the brain's attempt to re-establish communication between networks through the recruitment of "detour pathways" using less established routes to bypass prior, now damaged, connections. While a growing number of studies demonstrate hyperconnectivity following concussion (Borich et al, 2015;Newsome et al, 2016;Manning et al, 2017), these studies tend to focus on increases in the density of connections. To date there is no study explicitly demonstrating the formation of re-routing patterns via an effective connectivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we noted: a) alterations within the default mode network; b) increased connectivity in the right frontal pole in the executive function network; and c) increased connectivity in the left frontal operculum cortex associated with the ventral attention network (Borich et al, 2015). Newsome et al (2016) found that asymptomatic adolescent athletes demonstrated increased connectivity (relative to a cohort of high school athletes with orthopedic injuries) between the posterior cingulate cortex and the ventral lateral prefrontal cortex, as well as between the right lateral parietal cortex and the lateral temporal cortex. More recently, Manning et al (2017) reported significant increases in resting state connectivity in the visual and cerebellar networks.…”
Section: Introductionmentioning
confidence: 88%
“…Specifically, we noted: (a) alterations within the default mode network; (b) increased connectivity in the right frontal pole in the executive function network; and (c) increased functional connectivity in the left frontal operculum cortex associated with the ventral attention network (Borich et al, 2015). Newsome et al (2016) found that asymptomatic adolescent athletes demonstrated increased connectivity (relative to a cohort of high school athletes with orthopedic injuries) between the posterior cingulate cortex and the ventral lateral prefrontal cortex, as well as between the right lateral parietal cortex and the lateral temporal cortex. More recently, Manning et al (2017) reported significant increases in resting state connectivity in the visual and cerebellar networks.…”
Section: Introductionmentioning
confidence: 87%
“…They propose that this response reflects the brain's attempt to re-establish communication between networks through the recruitment of "detour pathways" using less established routes to bypass prior, now damaged, connections. While a growing number of studies demonstrate hyperconnectivity following concussion (Borich et al, 2015;Newsome et al, 2016;Manning et al, 2017), these studies tend to focus on increases in the density of connections. To date there is no study explicitly demonstrating the formation of re-routing patterns via an effective connectivity analysis.…”
Section: Hyperconnectivity As a Feature Of Brain Injurymentioning
confidence: 99%